Pricing strategy : a study on STIDC Furniture Vendor under the STIDC Furniture Vendorship Development Programme (PPVP) in Sarawak / Mohammad Mubarak Abdillah Su'ut - Abdillah Su'ut, Mohammad Mubarak (2008)
This paper examines the issue of pricing strategy of STIDC Furniture Vendor Under The STIDC Furniture Vendorship Development Programme (PPVP) In Sarawak. The objectives if this study is firstly to identify types of pricing strategies available for STIDC furniture vendors, secondly, to identify the types of pricing strategies commonly used by STIDC furniture vendors and lastly to recommend suggestions to improve STIDC furniture vendors pricing strategy. 44 respondents were involved particularly STIDC furniture vendors in order to know the types of pricing strategy they currently adopt and to have their opinions and suggestions as well as recommendations to improve the pricing strategy of their furniture products in the market. Several techniques are used in order to identify their pricing strategy involving Frequency Distributions, Average Mean Score, Correlation Analysis and Cross Tabulations. Average Mean Score showed that Contribution Pricing has is the most common pricing strategy used by STIDC furniture vendors while correlation analysis shows that Target Pricing is the most significant relationship with the vendors' furniture product pricing in the market.